2021
DOI: 10.1136/bcr-2021-242766
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibitor-induced colitis: a case report and review of the literature

Abstract: A 72-year-old woman with metastatic ER/PR-positive breast cancer who had been on ribociclib and letrozole for 1 year developed severe life-threatening colitis. She presented to emergency department with features of acute abdomen and diarrhoea. The diagnosis of colitis was confirmed radiologically as well as by histopathological examination of the biopsy specimen and the patient clinically improved after withholding ribociclib and receiving corticosteroids compatible with ribociclib-induced colitis. The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several antagonists with excellent activity against CDK4 and CDK6 have been approved for treatment of breast cancer, which restore cell cycle control at the G1/S transition and significantly extend patients' lives [12,[25][26][27][28]. Furthermore, the clinical benefits of these inhibitors for lung cancer patients are currently under evaluation, and promising results have been observed in certain subtypes of lung cancer patients [29][30][31]. In the current study, we found that decreased FAM117A expression in lung cancer cells warrants cell cycle progression by releasing the G1/S checkpoint, which could be fully rescued by CDK4/6 inhibitors and provides a molecular basis for treatment of lung cancer patients with CDK inhibitors or other cell cycle modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Several antagonists with excellent activity against CDK4 and CDK6 have been approved for treatment of breast cancer, which restore cell cycle control at the G1/S transition and significantly extend patients' lives [12,[25][26][27][28]. Furthermore, the clinical benefits of these inhibitors for lung cancer patients are currently under evaluation, and promising results have been observed in certain subtypes of lung cancer patients [29][30][31]. In the current study, we found that decreased FAM117A expression in lung cancer cells warrants cell cycle progression by releasing the G1/S checkpoint, which could be fully rescued by CDK4/6 inhibitors and provides a molecular basis for treatment of lung cancer patients with CDK inhibitors or other cell cycle modulators.…”
Section: Discussionmentioning
confidence: 99%